Analysis of the Impacts of Land Reforms on Urban Development in Kenya - Ngetich, J. K. (Africa Environmental Review Journal, 2017)
Land reform is an emotive cross-cutting issue especially in Africa. Land reform is viewed in the context of establishment of secure and formalized property rights in land and redistribution of property rights. Over the last two decades, Kenya has carried out a number of land reforms touching on urban land with the major milestones being the formulation of land policy and its entrenchment in the Constitution of Kenya 2010; establishment of an independent National Land Commission (NLC); and reducing land leases from 999 years to 99 years. Despite huge investment made in land reform agenda, not much has been achieved in the improvement of the welfare of its citizens especially in the Urban areas, as evidenced by over 70% of the population languishing in poverty and living in informal settlements. The proposal to issue out 3 million titles by 2017 is yet to be achieved and that land owners will have to wait for long to access resources for development due to lack of collateral security. This paper therefore reviews and analyses the impacts of land reforms in Kenya and its implications on urban land development. It gives suggestions on what needs to be done to make land reform process succeed and be beneficial to all.